Analyzing the potential targets and mechanisms of liver damage induced by acetyl tributyl citrate plasticizer using network toxicology, molecular docking and in vitro experiments - Guo, Dong-qun; Fang, Yu-ming; Sun, Zhen-dong; Zeng, Ya-fen; Wang, Gui-dan; Liang, Jin-wei (Frontiers in Pharmacology, 2025)
BackgroundAcetyl tributyl citrate (ATBC) may have adverse effects on liver health; however, the underlying mechanisms and pathophysiology remain unclear. The objective of this study was to elucidate the complex effects of ATBC on the liver and to determine the underlying molecular mechanisms by which environmental pollutants affect the disease process.MethodsWe used network toxicology and molecular docking techniques to analyze potential targets and mechanisms of liver injury caused by ATBC plasticizer. Potential targets associated with ATBC exposure and liver injury were identified by using ChEMBL, STITCH, GeneCards and OMIM databases. Enrichment analysis was performed using the DAVID database (https://david.ncifcrf.gov/) to identify biological pathways associated with these genes. Finally, transcription quantitative polymerase chain reaction, CCK-8 assay, Western blot, and immunofluorescence staining were used to assess the effect of candidate potential targets on liver injury.ResultsA total of 74 common targets associated with ATBC and liver injury were obtained. Enrichment analysis emphasized the association between these plastocyanin-targeted genes and the apoptotic pathway, suggesting that plastocyanin has a broad impact on cell survival. Moreover, molecular docking analysis demonstrated that ATBC exhibited a specific binding affinity for TNF-α, thereby suggesting that TNF-α plays a pivotal role in the regulation of liver damage pathogenesis. In vitro experiments further validated the expression of this molecule with the apoptosis marker molecules BAX and Bcl2 in ATBC-induced liver injury.ConclusionThe study suggests that TNF-α is involved in the process of ATBC-induced liver damage and may be related to cell apoptosis.